Autophagy impairment by Helicobacter pylori‐induced methylation silencing of MAP1LC3Av1 promotes gastric carcinogenesis. Issue 10 (14th March 2017) - Muhammad, Jibran Sualeh; Nanjo, Sohachi; Ando, Takayuki; Yamashita, Satoshi; Maekita, Takao; Ushijima, Toshikazu; Tabuchi, Yoshiaki; Sugiyama, Toshiro
Abstract : Helicobacter pylori ( H. pylori ) infection induces methylation silencing of tumor suppressor genes causing gastric carcinogenesis. Impairment of autophagy induces DNA damage leading to genetic instability and carcinogenesis. We aimed to identify whether H. pylori infection induced methylation silencing of host autophagy‐related ( Atg ) genes, impairing autophagy and enhancing gastric carcinogenesis. Gastric mucosae were obtained from 41 gastric cancer patients and 11 healthy volunteers (8 H. pylori ‐uninfected and 3 H. pylori ‐infected). Methylation status of Atg genes was analyzed by a methylation microarray and quantitative methylation‐specific PCR (qMSP); mRNA expression was assessed by quantitative reverse transcription PCR (qRT‐PCR). Cell proliferation, migration and invasion were assessed in normal rat gastric epithelial cells. Gene knock‐down was performed by siRNA. Autophagy was assessed by western blotting. Of 34 Atg genes, MAP1LC3A variant 1 (MAP1LC3Av1) and ULK2 were identified by methylation microarray analysis as exhibiting specific methylation in H. pylori ‐infected mucosae and gastric cancer tissues. Methylation silencing of MAP1LC3Av1 was confirmed by qMSP, qRT‐PCR and de‐methylation treatment in two gastric cancer cell lines. Knock‐down of map1lc3a, the rat homolog of the human MAP1LC3Av1, inhibited autophagy response and increased cell proliferation, migration and invasion in normal rat gastric epithelial cells, despite the presence of map1lc3b, the rat homolog of the human MAP1LC3B gene important for autophagy. Furthermore, MAP1LC3Av1 was methylation‐silenced in 23.3% of gastric cancerous mucosae and 40% of non‐cancerous mucosae with H. pylori infection. MAP1LC3Av1 is essential for autophagy and H. pylori ‐induced methylation silencing of MAP1LC3Av1 may impair autophagy, facilitating gastric carcinogenesis. Abstract : What's new? Helicobacter pylori infection has been shown to induce methylation silencing of tumor suppressor genes, causing gastric carcinogenesis. On the other side, impairment of autophagy induces DNA damage, leading to genetic instability and carcinogenesis. Here, the authors show that the host autophagy‐related gene MAP1LC3Av1 is specifically methylation‐silenced in H. pylori ‐infected non‐cancerous and cancerous gastric mucosae. Inactivation of map1lc3a, a rat homolog of the human MAP1LC3Av1, disrupts the autophagy pathway, leading to carcinogenesis in gastric epithelial cells. MAP1LC3Av1 methylation and expression levels could potentially be used as an early indicator of carcinogenic transformation of non‐cancerous mucosae in H. pylori ‐infected gastric cancer patients.